Dietary supplementation patterns of Korean Olympic athletes participating in the Beijing 2008 Summer Olympic Games - Kim, J.; Kang, S.-K.; Jung, H. S.; Chun, Y.-S.; Trilk, J. L.; Jung, S. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
Athletes report frequent use of various dietary supplements (DSs). However, no study has examined DS use and antidoping knowledge in Korean Olympians. The objectives of this study were to obtain information about Korean Olympians` DS use during the training period for the Beijing 2008 Summer Olympic Games and immediately before their Olympic events, to obtain DS-intake reasons and DS providers, and to obtain information on athletes` doping education, knowledge, and educators. Korean Olympians completed 2 questionnaires 1 wk before the opening and within 1 wk after the closing of the Beijing 2008 Summer Olympic Games. Results showed that 79% of male and 82% of female Olympians take more than 1 DS during the training period and that vitamins and Oriental supplements are the 2 top-ranked DSs. Reasons for DS use were to improve recovery ability (66%) and muscle performance (22%), and sources of obtaining DSs were parents (36%) and coaches (35%). Furthermore, 79% of Korean Olympians reported receiving regular education on antidoping regulations from Olympic-sponsored education classes (64%) and coaches (15%). In conclusion, this study was the first to examine DS use and antidoping-related information in Korean Olympians. Because some herbal products contain substances banned by the World Anti-Doping Agency, athletes should be cautious in using mixed Oriental supplements.